A magnetic separation layer aggregation-induced luminescence coded microsphere and its preparation method and application

By packing oil -soluble AIE molecules in the blank polymer microspheres and forming a magnetic separation layer, combined with electrostatic adsorption method attached to the water -soluble ACQ molecules, to prepare a high -encoding capacity of magnetic separation layer The problem of limited coding ability and insufficient material stability in technology.

CN118033125BActive Publication Date: 2025-01-28AIE INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410149594.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-01
Publication Date
2025-01-28
Estimated Expiration
2044-02-01

AI Technical Summary

Technical Problem

In the prior art, the encoding capability of quantum dot-encoded microspheres is limited by the reabsorption and color-sequential effects between fluorescence signals. Traditional organic materials experience fluorescence quenching in the aggregation state, limiting the encoding capacity and stability.

Method used

Adopt a magnetic separation layer to gather induced luminous (AIE) materials, and to bury the oil -soluble AIE molecule in the blank polymer microspheres through the active swelling method to form a magnetic separation layer. The magnetic separation layer of the capacity gathers the light -emitting encoding of microspheres.

Benefits of technology

The magnetic separation layer of high -coding capacity, stringless color effects and fluorescent intensity agglomerate induced light -emitting coding microspheres, solve the problem of fluorescence ingenuity in traditional materials, and improve the stability and capacity of coding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118033125B_ABST
    Figure CN118033125B_ABST
Patent Text Reader

Abstract

The present invention discloses a magnetic separation layer aggregation induced luminescence coded microsphere and its preparation method and application; the magnetic separation layer aggregation induced luminescence coded microsphere comprises AIE polymer microsphere, water-soluble ACQ molecule and magnetic particles; the AIE polymer microsphere is obtained by embedding oil-soluble AIE molecule inside blank polymer microsphere, the magnetic particles are deposited on the surface of AIE polymer microsphere to form a magnetic separation layer, and the water-soluble ACQ molecule is attached to the surface of the magnetic separation layer; the difference between the maximum emission wavelength of the oil-soluble AIE molecule and the maximum emission wavelength of the water-soluble ACQ molecule is in the range of 130nm to 290nm. The encoding capacity of the magnetic separation layer aggregation induced luminescence magnetic coded microsphere of the present invention is ≥14 times, and the CV value of the flow fluorescence signal and the CV value of the flow FCS are both less than 10%; an important fluorescent material is added to the coding element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of in vitro diagnosis, and in particular relates to a magnetic separation layer aggregation-induced luminescence coded microsphere and a preparation method and application thereof. Background Art

[0002] The development and completion of the human genome and proteome in recent years has led to a huge demand for large-scale analysis of biomolecules, which has promoted the rapid development of liquid suspension biochips with encoded microspheres as the core. Liquid suspension biochips with rapid high-throughput flow cytometry and magnetic separation as analytical methods have gradually become a new goal for accurate diagnosis by performing rapid and high-throughput multiplex detection of markers such as proteins, nucleic acids and small molecules. Among them, the development of encoded microspheres with high encoding capacity and stability is still a huge challenge. The design of suitable encoded microspheres has the following requirements: high photostability, good anti-magnetism, large number of codes, no reabsorption and crosstalk effects, etc.

[0003] Spectral signals are widely used in the construction of liquid biochips due to their flexible encoding and fast decoding speed. At present, the commonly used spectral encoding materials are mainly organic materials, quantum dots, upconversion dots and photonic crystals, etc. Quantum dots have become popular encoding materials due to their high brightness and narrow emission spectrum, but the encoding ability of quantum dots is limited by the reabsorption and cross-color effect between quantum dot fluorescence signals, which limits the application of quantum dot encoding microspheres.

[0004] At present, commercial liquid biochip Luminex system and BD's cytometric bead array all use organic dyes for encoding, but traditional organic materials have fluorescence quenching in the aggregated state, which limits the encoding capacity and stability of traditional organic materials. The new aggregation-induced emission (AIE) material discovered by the team of Academician Tang Benzhong in 2001 is a promising encoding material for the preparation of encoded microspheres, because AIE materials can achieve in-situ enhancement of fluorescence signals during the aggregation process. Aggregation-induced emission materials have properties such as large Stokes shift, strong resistance to photobleaching, and anti-magnetism, and are an excellent encoding microsphere material. However, there are few public reports on the efficient preparation of magnetic fluorescence encoding using AIE materials. Therefore, it is very necessary to develop a technology for the efficient and direct generation of aggregation-induced emission magnetic encoded microspheres. Summary of the invention

[0005] In order to solve the shortcomings of the prior art, the present invention aims to provide a magnetic separation layer aggregation-induced luminescence coded microsphere and its preparation method and application. The prepared magnetic separation layer aggregation-induced luminescence coded microsphere has the characteristics of high coding capacity, no cross-color effect and high fluorescence intensity.

[0006] The technical solution adopted by the present invention is:

[0007] A magnetic separation layer aggregation-induced luminescence magnetic encoding microsphere, comprising AIE polymer microspheres, water-soluble ACQ molecules and magnetic particles, wherein the AIE polymer microspheres are obtained by embedding oil-soluble AIE molecules inside blank polymer microspheres, the magnetic particles are deposited on the surface of the AIE polymer microspheres to form a magnetic separation layer, and the water-soluble ACQ molecules are attached to the surface of the magnetic separation layer;

[0008] The difference between the maximum emission wavelength of the oil-soluble AIE molecule and the maximum emission wavelength of the water-soluble ACQ molecule is in the range of 130 nm to 290 nm.

[0009] Preferably, the blank polymer microspheres are selected from at least one of polystyrene microspheres, polymethyl methacrylate microspheres and polyglycidyl acrylate microspheres;

[0010] Further preferably, the blank polymer microspheres are selected from polystyrene microspheres or polyglycidyl acrylate microspheres.

[0011] Preferably, the magnetic particles are Fe3O4;

[0012] Preferably, the oil-soluble AIE molecule is selected from at least one of the following AIE-IR1 to AIE-IR10 molecules:

[0013]

[0014] The water-soluble ACQ molecule is selected from at least one of the following: APC (allophycocyanin), Cy5, Cy7, rhodamine, PE, PE-Alexa Flour 610, PE-Alexa Flour 647, and FITC.

[0015] Preferably, the oil-soluble AIE molecules are embedded in the blank polymer microspheres by an active swelling method, and the amount of the oil-soluble AIE molecules in the active swelling method is 0.01 wt% to 10 wt% of the amount of the blank polymer microspheres;

[0016] Further preferably, the active swelling method is to allow the oil-soluble AIE molecules to swell with the blank polymer microspheres via a swelling agent so that the oil-soluble AIE molecules are embedded inside the blank polymer microspheres;

[0017] More preferably, in the active swelling method, the swelling agent is selected from at least one of dichloromethane, tetrahydrofuran, chloroform, anisole, benzyl alcohol and toluene, and the particle size of the blank polymer microspheres ranges from 0.03 μm to 50 μm;

[0018] More preferably, the particle size of the blank polymer microspheres ranges from 0.5 μm to 10 μm.

[0019] Preferably, the magnetic particles are deposited on the surface of the AIE polymer microspheres by an in-situ precipitation method of iron salts, wherein the amount of iron salts used in the in-situ precipitation method is 0.1 wt% to 25 wt% of the amount of blank polymer microspheres;

[0020] Further preferably, the in-situ precipitation method is to add an alkaline solution to react with the iron salt chelated on the surface of the AIE polymer microspheres to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres;

[0021] More preferably, in the in-situ precipitation method, the surface of the AIE polymer microspheres is modified by sulfonation, the alkaline solution is selected from at least one of sodium hydroxide solution, ammonia water, potassium hydroxide solution and sodium bicarbonate solution; the iron salt is selected from at least one of a trivalent iron salt and a divalent iron salt; the trivalent iron salt is selected from at least one of ferric chloride hexahydrate and anhydrous ferric chloride; the divalent iron salt is selected from at least one of ferrous chloride tetrahydrate, ferrous chloride dihydrate, ferrous sulfate and ferrous sulfate heptahydrate.

[0022] More preferably, considering the uniformity of magnetic particles deposited on the surface of the AIE polymer microspheres, the iron salt is a compound of a trivalent iron salt and a divalent iron salt, wherein the mass amount of the trivalent iron salt is 10% to 60% of the mass amount of the divalent iron salt.

[0023] Preferably, the water-soluble ACQ molecules are attached to the surface of the magnetic separation layer by electrostatic adsorption; the mass amount of the oil-soluble AIE molecules accounts for 0.01wt% to 1000wt% of the mass amount of the water-soluble ACQ molecules.

[0024] Further preferably, the electrostatic adsorption method is to add the AIE polymer microspheres with a magnetic separation layer deposited on the surface into a water-soluble ACQ molecule aqueous solution to react so that the water-soluble ACQ molecules are attached to the surface of the magnetic separation layer through electrostatic adsorption.

[0025] Preferably, the encoding capacity of the magnetic separation layer aggregation-induced luminescence magnetic encoding microspheres is ≥14, and the CV value of the flow fluorescence signal and the CV value of the flow FCS are both less than 10%.

[0026] The preparation method of the above-mentioned magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres comprises the following steps:

[0027] S1. Preparation of AIE polymer microspheres by active swelling method

[0028] (1) dispersing blank polymer microspheres in water to obtain a microsphere dispersion;

[0029] (2) dissolving the oil-soluble AIE molecule in a swelling agent to obtain an AIE swelling agent solution;

[0030] (3) adding the AIE swelling agent solution described in step (2) to the microsphere dispersion described in step (1), and after ultrasonic treatment, closing the reactor to carry out swelling reaction. After the reaction is completed, volatilizing and removing the swelling agent to obtain AIE polymer microspheres;

[0031] S2. Preparation of magnetic AIE polymer microspheres by in situ precipitation method

[0032] The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is increased for reaction, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation modification on the surface, the AIE polymer microspheres are mixed with iron salt and water for reaction, and the supernatant is removed by centrifugation to obtain iron salt chelated AIE polymer microspheres, an alkaline solution is added, the temperature is increased, and the iron salt reacts in situ to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres to form a magnetic separation layer, and magnetic separation is performed to obtain magnetic AIE polymer microspheres;

[0033] S3. Preparation of magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres by electrostatic adsorption of ACQ molecules

[0034] The water-soluble ACQ molecules are dissolved in water to obtain an ACQ aqueous solution, and the magnetic AIE polymer microspheres obtained in step S2 are added thereto. After stirring for reaction, the supernatant is removed by centrifugation to prepare magnetic separation layer aggregation-induced luminescence magnetic encoded microspheres.

[0035] Preferably, the method for preparing the magnetic separation layer aggregation-induced luminescence coded microspheres comprises the following steps:

[0036] S1. Preparation of AIE polymer microspheres by active swelling method

[0037] (1) dispersing blank polymer microspheres in water to obtain a microsphere dispersion;

[0038] (2) dissolving the oil-soluble AIE molecule in a swelling agent to obtain an AIE swelling agent solution;

[0039] (3) adding the AIE swelling agent solution described in step (2) to the microsphere dispersion described in step (1), and after ultrasonic treatment at an ultrasonic power of 50 W to 400 W for 1 min to 30 min, a closed reactor is used for swelling reaction for 0.5 h to 4 h. After the reaction is completed, the swelling agent is volatilized to obtain AIE polymer microspheres;

[0040] S2. Preparation of magnetic AIE polymer microspheres by in situ precipitation method

[0041] The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is raised to 30°C to 100°C and the reaction is carried out for 4h to 12h, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation modification on the surface, the AIE polymer microspheres are mixed with iron salt and water, and the mixture is immersed in the solution for reaction for 0.5h to 10h, and the supernatant is removed by centrifugation to obtain iron salt chelated AIE polymer microspheres, an alkaline solution is added, the temperature is raised to 60°C to 120°C and the reaction is carried out for 0.5h to 4h, the iron salt reacts in situ to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres to form a magnetic separation layer, and magnetic separation is carried out to obtain magnetic AIE polymer microspheres;

[0042] S3. Preparation of magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres by electrostatic adsorption of ACQ molecules

[0043] The water-soluble ACQ molecules are dissolved in water to obtain an ACQ aqueous solution, and the magnetic AIE polymer microspheres obtained in step S2 are added thereto. After stirring at 25° C. to 50° C. for 0.5 to 4 hours, the supernatant is removed by centrifugation to prepare magnetic separation layer aggregation-induced luminescence magnetic encoded microspheres.

[0044] Further preferably, in step S1, the ultrasonic power of step (3) is 300W, the ultrasonic treatment time is 5 minutes, and the time for volatilizing and removing the swelling agent is 2 hours to 10 hours. More preferably, the time for volatilizing and removing the swelling agent is 4 hours.

[0045] Further preferably, in step S2, the soaking reaction time is 2 h to 4 h.

[0046] Further preferably, in step S2, the reaction temperature after the AIE polymer microspheres are dissolved in the sulfuric acid solution is 60°C to 90°C.

[0047] Preferably, in step S1, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.1% to 20% of the mass amount of water;

[0048] Further preferably, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.5% to 10% of the mass amount of water.

[0049] Preferably, in step S1, the mass amount of the oil-soluble AIE molecules in the AIE swelling agent solution is 0.1% to 50% of the mass amount of the swelling agent;

[0050] Preferably, in step S2, the mass concentration of the sulfuric acid solution is 80% to 90%; the mass amount of the AIE encoded microspheres is 1% to 30% of the mass amount of the sulfuric acid solution;

[0051] Further preferably, the mass concentration of the sulfuric acid solution is 98.3%; and the mass amount of the AIE polymer microspheres is 5% to 20% of the mass amount of the sulfuric acid solution.

[0052] Preferably, in step S2, the mass dosage of the iron salt is 0.0005% to 25% of the mass dosage of water; the mass dosage of the alkaline solution is 0.1% to 50% of the mass dosage of water; the mass concentration of the alkaline solution is 1% to 10%;

[0053] Preferably, in step S3, the ACQ molecular weight dosage of the ACQ aqueous solution is 0.001% to 1% of the water weight dosage.

[0054] Preferably, the water in step S1, step S2 and step S3 is ultrapure water; the centrifugal speed is 3000 rpm to 6000 rpm, the centrifugal time is 5 min to 60 min, and the number of centrifugation is more than three times.

[0055] The above-mentioned magnetic separation layer aggregation-induced luminescence coded microspheres are used in in vitro non-disease diagnostic detection.

[0056] The present invention proposes a new technology for efficiently preparing dual-wavelength magnetically encoded microspheres by combining swelling adsorption, in-situ generation and electrostatic adsorption. The oil-soluble AIE molecules are swollen into the interior of the microspheres through hydrophobic interaction and concentration difference, magnetic particles are generated on the surface of the microspheres by an in-situ generation method of iron salts, and water-soluble ACQ molecules are electrostatically adsorbed on the surface of the magnetic microspheres. At the same time, by selecting the wavelengths of the oil-soluble AIE molecules and the water-soluble ACQ molecules, dual-wavelength, high-encoding-capacity magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres with uniform particle size are obtained. The microspheres have excellent detection stability and can achieve 14 or more encodings.

[0057] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:

[0058] (1) Compared with the fluorescent materials of traditional magnetically encoded microspheres, the AIE materials of the magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres of the present invention improve the encoding capacity of the magnetically encoded microspheres and solve the problem of fluorescence reabsorption effect of traditional fluorescent materials inside the microspheres. At the same time, the oil-soluble AIE molecules are embedded inside the microspheres to prevent the leakage of the dye.

[0059] (2) The present invention uses a simple swelling volatilization and in-situ generation technology to encapsulate high-concentration AIE molecules inside the microspheres, deposit magnetic particles in-situ on the surface of the microspheres, and use electrostatic action to adsorb water-soluble ACQ molecules. At the same time, there is a magnetic separation layer between the AIE molecules and the ACQ molecules, which effectively isolates the incompatibility between the hydrophilic and hydrophobic molecules. By separately regulating the AIE molecules and ACQ molecular components, dual-wavelength magnetic fluorescent encoded microspheres with optimal performance are obtained.

[0060] (3) Generally speaking, the traditional ACQ dual-wavelength fluorescent material will have a strong FRET process due to simultaneous adsorption on the surface of the microsphere, resulting in fluorescence attenuation. The present invention utilizes the in-situ generation of magnetic particles, and due to the isolation effect of the magnetic separation layer, the FRET effect of the AIE molecules and the ACQ molecules is greatly reduced. At the same time, the AIE material has a typical aggregation-induced emission property. The AIE molecules are embedded in the microspheres and can emit strong fluorescence in the aggregate.

[0061] (4) The preparation method of the magnetic separation layer aggregation-induced luminescence magnetic encoded microspheres of the present invention is simple. By utilizing oil-soluble AIE molecules and water-soluble ACQ molecules and the insulating effect of the magnetic separation layer, dual-wavelength high-coding capacity magnetic encoded microspheres are obtained, thereby realizing the effective application of AIE molecules in the preparation of encoded microspheres, adding an important fluorescent material to the coding elements, and providing a new coding strategy for the core raw materials of protein biochips. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is a scanning electron microscope image of the dual-wavelength magnetically encoded microspheres prepared in Example 1.

[0063] Figure 2 This is the emission spectrum of AIE molecules and ACQ molecules in the dual-wavelength magnetically encoded microspheres prepared in Example 1.

[0064] Figure 3 Schematic diagram of flow encoding of dual-wavelength magnetic encoding microspheres prepared in Example 1. DETAILED DESCRIPTION

[0065] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0066] The blank polymer microspheres in the examples and comparative examples are polystyrene polymer microspheres with a diameter of 5 μm, which are from AIE Research Institute and have a product number of NWKPB-500.

[0067] The room temperature in the examples and comparative examples was 25°C.

[0068] The encoding data of the aggregation-induced luminescence magnetically encoded microspheres were tested using an analytical flow cytometer. The CV value of the flow fluorescence signal represented the uniformity of the fluorescence swelling, and the CV value of the flow FCS represented the uniformity of the particle size of the microspheres. According to the detection performance requirements of in vitro diagnostics, the CV value of the flow fluorescence signal and the CV value of the flow FCS must be less than 10% to determine that the encoding was successful, otherwise it failed.

[0069] Example 1

[0070] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water to obtain a microsphere dispersion;

[0071] 5 mg of AIE-IR1 molecules were dissolved in 10 mL of tetrahydrofuran to obtain an AIE swelling agent solution; the two solutions were mixed together (the mass of AIE molecules accounted for 0.5 wt% of the mass of blank polymer microspheres), and ultrasonically treated at a power of 100 W for 1 min. After the closed swelling for 2 h, the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0072] Ferrous sulfate heptahydrate and ferric chloride hexahydrate were mixed in a mass ratio of 2:1, 100 mg in total, and 100 g of water. The AIE polymer microspheres with sulfonated surface were added. After soaking for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. The reaction was repeated three times to obtain iron salt chelated AIE polymer microspheres. 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80 ° C, and the reaction was continued for 2 hours. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. After magnetic separation, AIE magnetically encoded microspheres were obtained. 1 mg of fluorescein (APC) molecules were dissolved in 0.5 mL of water, and the obtained AIE magnetically encoded microspheres were added. After stirring at room temperature for 2 hours, the microspheres were centrifuged at 5000 rpm and resuspended in water. The reaction was repeated three times to obtain dual-wavelength aggregation-induced luminescence magnetically encoded microspheres.

[0073] The morphology of dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5 μm (e.g. Figure 1 The fluorescence spectrum of the dual-wavelength aggregation-induced emission magnetically encoded microspheres was tested using a fluorescence spectrometer. The AIE emission wavelength was 780 nm, and the ratio of the fluorescence intensity before and after the AIE molecule was coated was 1300. The ACQ molecule emission wavelength was 648 nm, and the ratio of the fluorescence intensity before and after the ACQ molecule was 1.1 (e.g. Figure 2 ), the difference in center wavelength is 132nm. The encoding data of dual-wavelength aggregation-induced luminescence magnetic encoded microspheres were tested using an analytical flow cytometer. The CV value of the tested flow fluorescence signal was 3.6%, the CV value of the flow FCS was 4.7%, and the encoding peak was 14-fold (such as Figure 3 ), encoding is successful.

[0074] Comparative Example 1

[0075] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water to obtain a microsphere dispersion;

[0076] 5 mg of AIE-IR1 molecules and 1 mg of fluorescein (APC) molecules were dissolved in 10 mL of tetrahydrofuran to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, sealed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm, and then resuspended in water, and repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0077] Ferrous sulfate heptahydrate and ferrous chloride hexahydrate (100 mg, mass ratio 2:1) were mixed with 100 g of water, and the above-obtained AIE polymer microspheres with sulfonation modification were added. After soaking for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. The reaction was repeated three times to obtain iron salt chelated AIE polymer microspheres. 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was carried out for 2 hours. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. After magnetic separation, dual-wavelength aggregation-induced luminescence magnetically encoded microspheres were obtained.

[0078] The morphology of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. Due to the incompatibility of the hydrophilicity and hydrophobicity of the AIE molecules and the ACQ molecules, the ACQ molecules could not enter the microspheres. The encoding data of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the flow fluorescence signal tested was 20.6%, and the CV value of the flow FCS was 7.7%, indicating that the encoding failed.

[0079] Comparative Example 2

[0080] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water to obtain a microsphere dispersion;

[0081] 5 mg of Cy7 molecules were dissolved in 10 mL of tetrahydrofuran to obtain an ACQ swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, and after the swelling was closed for 2 h, the solvent was evaporated open for 4 h, and the supernatant was removed by centrifugation to obtain ACQ polymer microspheres. The obtained ACQ polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at a speed of 5000 rpm, and then resuspended in water, and repeated three times to obtain ACQ polymer microspheres with sulfonated surface modification.

[0082] Ferrous sulfate heptahydrate and ferric chloride hexahydrate were mixed in a mass ratio of 2:1, 100 mg in total, and 100 g of water. The ACQ polymer microspheres with sulfonated surface were added. After soaking for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. The reaction was repeated three times to obtain ACQ polymer microspheres chelated with iron salts. 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80 ° C, and the reaction was continued for 2 hours. The iron salts reacted in situ to generate magnetic particles that were deposited on the surface of the ACQ polymer microspheres. After magnetic separation, ACQ magnetically encoded microspheres were obtained. 1 mg of Cy5 molecules were dissolved in 0.5 mL of water, and the ACQ magnetically encoded microspheres were added. After stirring at room temperature for 2 hours, the microspheres were centrifuged at 5000 rpm and resuspended in water. The reaction was repeated three times to obtain dual-wavelength magnetically encoded microspheres.

[0083] The morphology of the dual-wavelength magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. Since the water-soluble ACQ molecules could not swell into the microspheres, the swelling experiment failed, and magnetically encoded microspheres with only ACQ molecules adsorbed on the surface were obtained. The encoding data of the dual-wavelength magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the flow fluorescence signal tested was 18.6%, and the CV value of the flow FCS was 27.7%, indicating encoding failure.

[0084] Comparative Example 3

[0085] Weigh 1 g of blank polymer microspheres and disperse them in 100 g of water to obtain a microsphere dispersion;

[0086] 5 mg of AIE-IR1 molecules were dissolved in 10 mL of tetrahydrofuran to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, and after the closed swelling for 2 h, the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0087] Ferrous sulfate heptahydrate and ferric chloride hexahydrate were mixed in a mass ratio of 2:1, 100 mg in total, and 100 g of water. The AIE polymer microspheres with sulfonated surface modification obtained above were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. The reaction was repeated three times to obtain iron salt chelated AIE polymer microspheres. 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80 ° C, and the reaction was carried out for 2 hours. The iron salt reacted in situ to generate magnetic particles deposited on the surface of the AIE polymer microspheres. After magnetic separation, AIE magnetically encoded microspheres were obtained. 1 mg of AIE-IR2 was dissolved in 0.5 mL of water, and the obtained AIE magnetically encoded microspheres were added. After stirring at room temperature for 2 hours, the microspheres were centrifuged at 5000 rpm and resuspended in water. After repeating three times, dual-wavelength aggregation-induced luminescence magnetically encoded microspheres were obtained.

[0088] The morphology of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. Since the solubility of AIE molecules in water is very low, they cannot be adsorbed onto the surface of the microspheres. The encoding data of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the flow fluorescence signal tested was 23.6%, and the CV value of the flow FCS was 14.3%, indicating encoding failure.

[0089] The results of the microspheres encoded with different fluorescent materials in Example 1 and Comparative Examples 1-3 are shown in Table 1.

[0090] Table 1 Effects of different wavelengths of AIE molecules and ACQ molecules and embedding positions on the encoding results

[0091]

[0092]

[0093] Example 2

[0094] Weigh 0.5 g of blank polymer microspheres and disperse them in 50 g of water to obtain a microsphere dispersion;

[0095] 5 mg of AIE-IR4 molecules were dissolved in 5 mL of dichloromethane to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, closed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 30 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0096] The total mass of 0.05g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 50g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification were added. After soaking for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres. 30mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was continued for 2h. The iron salt reacted in situ to generate magnetic particles deposited on the surface of the AIE polymer microspheres. After magnetic separation, AIE magnetically encoded microspheres were obtained. 5mg of Cy5 molecules were dissolved in 1mL of water, and the obtained AIE magnetically encoded microspheres were added. After stirring at room temperature for 2h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain dual-wavelength aggregation-induced luminescence magnetically encoded microspheres.

[0097] The morphology of dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. The fluorescence spectrum of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using a fluorescence spectrometer. The AIE emission wavelength was 900nm, and the ratio of the fluorescence intensity before and after the AIE molecule was coated was 1100. The ACQ molecule emission wavelength was 664nm, and the ratio of the fluorescence intensity before and after the ACQ molecule was coated was 1.1. The difference in central wavelength was 236nm. The encoding data of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the tested flow fluorescence signal was 4.6%, the CV value of the flow FCS was 5.7%, the encoding peak was 14-fold, and the encoding was successful.

[0098] Example 3

[0099] Weigh 1 g of blank polymer microspheres and disperse them in 75 g of water to obtain a microsphere dispersion;

[0100] 25 mg of AIE-IR3 molecules were dissolved in 7.5 mL of dichloromethane to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 5 min, closed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 75 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0101] The total mass of 0.15g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 100g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification obtained above were added. After soaking and reacting for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres; 75mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was continued for 2h. The iron salt reacted in situ to generate magnetic particles deposited on the surface of the AIE polymer microspheres; after magnetic separation, AIE magnetically encoded microspheres were obtained. 25mg of FITC molecules were dissolved in 5mL of water, and the obtained AIE magnetically encoded microspheres were added. After stirring at room temperature for 2h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain dual-wavelength aggregation-induced luminescence magnetically encoded microspheres.

[0102] The morphology of dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. The fluorescence spectrum of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using a fluorescence spectrometer. The AIE emission wavelength was 790nm, and the ratio of the fluorescence intensity before and after the AIE molecule was coated was 1150. The ACQ molecule emission wavelength was 520nm, and the ratio of the fluorescence intensity before and after the ACQ molecule was coated was 1.3. The difference in central wavelength was 270nm. The encoding data of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the tested flow fluorescence signal was 5.6%, the CV value of the flow FCS was 3.7%, the encoding peak was 14-fold, and the encoding was successful.

[0103] Example 4

[0104] Weigh 2.5 g of blank polymer microspheres and disperse them in 150 g of water to obtain a microsphere dispersion;

[0105] AIE-IR4 molecules of 50 mg mass were dissolved in 15 mL tetrahydrofuran to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 5 min, closed and swollen for 2 h, and then the solvent was evaporated for 6 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm, and then resuspended in water, and repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0106] A total mass of 0.5 g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 75 g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification obtained above were added. After soaking and reacting for 1 hour, the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain iron salt chelated AIE polymer microspheres; 50 mL of 1 mol / L sodium hydroxide solution was added, the temperature was raised to 80 ° C, and the reaction was continued for 2 hours. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres; after magnetic separation, AIE magnetically encoded microspheres were obtained. 50 mg of Cy5 molecules were dissolved in 5 mL of water, and the obtained AIE magnetically encoded microspheres were added. After stirring at room temperature for 2 hours, the microspheres were centrifuged at 5000 rpm and resuspended in water. This was repeated three times to obtain dual-wavelength aggregation-induced luminescence magnetically encoded microspheres.

[0107] The morphology of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. The fluorescence spectrum of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using a fluorescence spectrometer. The AIE emission wavelength was 900nm, and the ratio of the fluorescence intensity before and after the AIE molecule was coated was 1150. The ACQ molecule emission wavelength was 664nm, and the ratio of the fluorescence intensity before and after the ACQ molecule was coated was 1.5. The difference in central wavelength was 236nm. The encoding data of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the tested flow fluorescence signal was 3.5%, the CV value of the flow FCS was 3.8%, the encoding peak was 14-fold, and the encoding was successful.

[0108] Example 5

[0109] Weigh 10 g of blank polymer microspheres and disperse them in 500 g of water to obtain a microsphere dispersion;

[0110] 150 mg of AIE-IR5 molecules were dissolved in 25 mL of dichloromethane to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 10 min, closed and swollen for 2 h, and then the solvent was evaporated for 10 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 100 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0111] The total mass of 1g of ferrous chloride heptahydrate and ferric chloride hexahydrate was mixed with 50g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification were added. After soaking for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres. 100mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was continued for 2h. The iron salt reacted in situ to generate magnetic particles that were deposited on the surface of the AIE polymer microspheres. After magnetic separation, AIE magnetically encoded microspheres were obtained. 150mg of Cy5 molecules were dissolved in 10mL of water, and the obtained AIE magnetically encoded microspheres were added. After stirring at room temperature for 2h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain dual-wavelength aggregation-induced luminescence magnetically encoded microspheres.

[0112] The morphology of dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. The fluorescence spectrum of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using a fluorescence spectrometer. The AIE emission wavelength was 850nm, and the ratio of the fluorescence intensity before and after the AIE molecule was coated was 1350. The ACQ molecule emission wavelength was 664nm, and the ratio of the fluorescence intensity before and after the ACQ molecule was coated was 1.5. The difference in central wavelength was 186nm. The encoding data of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the tested flow fluorescence signal was 5.5%, the CV value of the flow FCS was 6.8%, the encoding peak was 14-fold, and the encoding was successful.

[0113] Example 6

[0114] Weigh 0.1 g of blank polymer microspheres and disperse them in 12.5 g of water to obtain a microsphere dispersion;

[0115] 1 mg of AIE-IR7 molecules were dissolved in 2 mL of chloroform to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, closed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 15 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0116] The total mass of 0.02g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 20g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification were added. After soaking for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres. 15mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was carried out for 2h. The iron salt reacted in situ to generate magnetic particles deposited on the surface of the AIE polymer microspheres. After magnetic separation, AIE magnetically encoded microspheres were obtained. 1mg of Cy5 molecules were dissolved in 0.5mL of water, and the obtained AIE magnetically encoded microspheres were added. After stirring at room temperature for 2h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain dual-wavelength aggregation-induced luminescence magnetically encoded microspheres.

[0117] The morphology of dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. The fluorescence spectrum of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using a fluorescence spectrometer. The AIE emission wavelength was 890nm, and the ratio of the fluorescence intensity before and after the AIE molecule was coated was 1450. The ACQ molecule emission wavelength was 664nm, and the ratio of the fluorescence intensity before and after the ACQ molecule was coated was 1.3. The difference in central wavelength was 226nm. The encoding data of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the flow fluorescence signal was 4.5%, the CV value of the flow FCS was 6.8%, the encoding peak was 14-fold, and the encoding was successful.

[0118] Example 7

[0119] Weigh 1 g of blank polymer microspheres and disperse them in 125 g of water to obtain a microsphere dispersion;

[0120] 50 mg of AIE-IR9 molecules were dissolved in 5 mL of dichloromethane to obtain an AIE swelling agent solution; the two solutions were mixed together, ultrasonically treated at a power of 100 W for 1 min, closed and swollen for 2 h, and then the solvent was evaporated for 4 h, and the supernatant was removed by centrifugation to obtain AIE polymer microspheres. The obtained AIE polymer microspheres were added to 50 mL of concentrated sulfuric acid (98.3 wt%), the temperature was raised to 80 ° C, and the reaction was carried out for 8 h; the microspheres were centrifuged at 5000 rpm and resuspended in water, and the reaction was repeated three times to obtain AIE polymer microspheres with sulfonated surface modification.

[0121] The total mass of 0.2g of ferrous sulfate heptahydrate and ferric chloride hexahydrate was mixed with 100g of water in a mass ratio of 2:1, and the AIE polymer microspheres with sulfonation modification were added. After soaking for 1h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain iron salt chelated AIE polymer microspheres. 50mL of 1mol / L sodium hydroxide solution was added, the temperature was raised to 80℃, and the reaction was continued for 2h. The iron salt reacted in situ to generate magnetic particles deposited on the surface of the AIE polymer microspheres. After magnetic separation, AIE magnetically encoded microspheres were obtained. 50mg of Cy5 molecules were dissolved in 10mL of water, and the obtained AIE magnetically encoded microspheres were added. After stirring at room temperature for 2h, the microspheres were centrifuged at 5000rpm and resuspended in water. The process was repeated three times to obtain dual-wavelength aggregation-induced luminescence magnetically encoded microspheres.

[0122] The morphology of dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was observed using a field emission SEM electron microscope. The microspheres showed a regular spherical structure with a statistical particle size of about 5μm. The fluorescence spectrum of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using a fluorescence spectrometer. The AIE emission wavelength was 855nm, and the ratio of the fluorescence intensity before and after the AIE molecule was coated was 1450. The ACQ molecule emission wavelength was 664nm, and the ratio of the fluorescence intensity before and after the ACQ molecule was coated was 1.4. The difference in central wavelength was 191nm. The encoding data of the dual-wavelength aggregation-induced luminescence magnetically encoded microspheres was tested using an analytical flow cytometer. The CV value of the tested flow fluorescence signal was 6.5%, the CV value of the flow FCS was 4.8%, the encoding peak was 14-fold, and the encoding was successful.

[0123] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. A magnetic separation layer aggregation-induced luminescence magnetically encoded microsphere, characterized in that: It comprises AIE polymer microspheres, water-soluble ACQ molecules and magnetic particles, wherein the AIE polymer microspheres are obtained by embedding oil-soluble AIE molecules inside blank polymer microspheres, the magnetic particles are deposited on the surface of the AIE polymer microspheres to form a magnetic separation layer, and the water-soluble ACQ molecules are attached to the surface of the magnetic separation layer; The difference between the maximum emission wavelength of the oil-soluble AIE molecule and the maximum emission wavelength of the water-soluble ACQ molecule is in the range of 130 nm to 290 nm.

2. The magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres according to claim 1, characterized in that: The blank polymer microspheres are selected from at least one of polystyrene microspheres, polymethyl methacrylate microspheres and polyglycidyl acrylate microspheres; The magnetic particles are Fe3O4; The oil-soluble AIE molecule is selected from at least one of the following AIE-IR1 to AIE-IR10 molecules: The water-soluble ACQ molecule is selected from at least one of the following: APC, Cy5, Cy7, rhodamine, PE, PE-AlexaFlour 610, PE-AlexaFlour 647, FITC.

3. The magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres according to claim 1, characterized in that: The oil-soluble AIE molecules are embedded in the blank polymer microspheres by an active swelling method, wherein the amount of the oil-soluble AIE molecules used in the active swelling method is 0.01 wt% to 10 wt% of the amount of the blank polymer microspheres; The magnetic particles are deposited on the surface of the AIE polymer microspheres by an in-situ precipitation method of iron salts, wherein the amount of iron salts used in the in-situ precipitation method is 0.1 wt% to 25 wt% of the amount of blank polymer microspheres; The water-soluble ACQ molecules are attached to the surface of the magnetic separation layer by electrostatic adsorption; The mass amount of the oil-soluble AIE molecules accounts for 0.01wt% to 1000wt% of the mass amount of the water-soluble ACQ molecules.

4. The magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres according to claim 3, characterized in that: The active swelling method is to allow the oil-soluble AIE molecules to swell with the blank polymer microspheres through a swelling agent so that the oil-soluble AIE molecules are embedded inside the blank polymer microspheres; The in-situ precipitation method is to add an alkaline solution to react with the iron salt chelated on the surface of the AIE polymer microspheres in situ to generate magnetic particles that are deposited on the surface of the AIE polymer microspheres; The electrostatic adsorption method is to add the AIE polymer microspheres with a magnetic separation layer deposited on the surface into a water-soluble ACQ molecule aqueous solution to react so that the water-soluble ACQ molecules are attached to the surface of the magnetic separation layer through electrostatic adsorption.

5. The magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres according to claim 4, characterized in that: In the active swelling method, the swelling agent is selected from at least one of dichloromethane, tetrahydrofuran, chloroform, anisole, benzyl alcohol and toluene, and the particle size of the blank polymer microspheres ranges from 0.03 μm to 50 μm; In the in-situ precipitation method, the surface of the AIE polymer microspheres is modified by sulfonation, the alkaline solution is selected from at least one of sodium hydroxide solution, ammonia water, potassium hydroxide solution and sodium bicarbonate solution; the iron salt is selected from at least one of trivalent iron salt and divalent iron salt; the trivalent iron salt is selected from at least one of ferric chloride hexahydrate and anhydrous ferric chloride; the divalent iron salt is selected from at least one of ferrous chloride tetrahydrate, ferrous chloride dihydrate, ferrous sulfate and ferrous sulfate heptahydrate.

6. The magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres according to claim 1, characterized in that: The encoding capacity of the magnetic separation layer aggregation-induced luminescence magnetic encoding microspheres is ≥14, and the CV value of the flow fluorescence signal and the CV value of the flow FCS are both less than 10%.

7. The method for preparing the magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres according to any one of claims 1 to 6, characterized in that: The steps include: S1. Preparation of AIE polymer microspheres by active swelling method (1) dispersing blank polymer microspheres in water to obtain a microsphere dispersion; (2) dissolving the oil-soluble AIE molecule in a swelling agent to obtain an AIE swelling agent solution; (3) adding the AIE swelling agent solution described in step (2) to the microsphere dispersion described in step (1), and after ultrasonic treatment, closing the reactor to carry out swelling reaction. After the reaction is completed, volatilizing and removing the swelling agent to obtain AIE polymer microspheres; S2. Preparation of magnetic AIE polymer microspheres by in situ precipitation method The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is increased for reaction, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation modification on the surface, the AIE polymer microspheres are mixed with iron salt and water for reaction, and the supernatant is removed by centrifugation to obtain iron salt chelated AIE polymer microspheres, an alkaline solution is added, the temperature is increased, and the iron salt reacts in situ to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres to form a magnetic separation layer, and magnetic separation is performed to obtain magnetic AIE polymer microspheres; S3. Preparation of magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres by electrostatic adsorption of ACQ molecules The water-soluble ACQ molecules are dissolved in water to obtain an ACQ aqueous solution, and the magnetic AIE polymer microspheres obtained in step S2 are added thereto. After stirring for reaction, the supernatant is removed by centrifugation to prepare magnetic separation layer aggregation-induced luminescence magnetic encoded microspheres.

8. The method for preparing the magnetic separation layer aggregation-induced luminescence coded microspheres according to claim 7, characterized in that: The following steps are involved: S1. Preparation of AIE polymer microspheres by active swelling method (1) dispersing blank polymer microspheres in water to obtain a microsphere dispersion; (2) dissolving the oil-soluble AIE molecule in a swelling agent to obtain an AIE swelling agent solution; (3) adding the AIE swelling agent solution described in step (2) to the microsphere dispersion described in step (1), and after ultrasonic treatment at an ultrasonic power of 50 W to 400 W for 1 min to 30 min, a closed reactor is used for swelling reaction for 0.5 h to 4 h. After the reaction is completed, the swelling agent is volatilized to obtain AIE polymer microspheres; S2. Preparation of magnetic AIE polymer microspheres by in situ precipitation method The AIE polymer microspheres of step S1 are dissolved in a sulfuric acid solution, the temperature is raised to 30°C to 100°C and the reaction is carried out for 4h to 12h, and the supernatant is removed by centrifugation to obtain AIE polymer microspheres with sulfonation modification on the surface, the AIE polymer microspheres are mixed with iron salt and water, and the mixture is immersed in the solution for reaction for 0.5h to 10h, and the supernatant is removed by centrifugation to obtain iron salt chelated AIE polymer microspheres, an alkaline solution is added, the temperature is raised to 60°C to 120°C and the reaction is carried out for 0.5h to 4h, the iron salt reacts in situ to generate magnetic particles which are deposited on the surface of the AIE polymer microspheres to form a magnetic separation layer, and magnetic separation is carried out to obtain magnetic AIE polymer microspheres; S3. Preparation of magnetic separation layer aggregation-induced luminescence magnetically encoded microspheres by electrostatic adsorption of ACQ molecules The water-soluble ACQ molecules are dissolved in water to obtain an ACQ aqueous solution, and the magnetic AIE polymer microspheres obtained in step S2 are added thereto. After stirring at 25° C. to 50° C. for 0.5 to 4 hours, the supernatant is removed by centrifugation to prepare magnetic separation layer aggregation-induced luminescence magnetic encoded microspheres.

9. The method for preparing the magnetic separation layer aggregation-induced luminescence coded microspheres according to claim 7, characterized in that: In step S1, the mass amount of blank polymer microspheres in the microsphere dispersion is 0.1% to 20% of the mass amount of water; In step S1, the mass amount of the oil-soluble AIE molecules in the AIE swelling agent solution is 0.1% to 50% of the mass amount of the swelling agent; In step S2, the mass concentration of the sulfuric acid solution is 80% to 90%; the mass amount of the AIE polymer microspheres is 1% to 30% of the mass amount of the sulfuric acid solution; In step S2, the mass dosage of the iron salt is 0.0005% to 25% of the mass dosage of water; the mass dosage of the alkaline solution is 0.1% to 50% of the mass dosage of water; the mass concentration of the alkaline solution is 1% to 10%; In step S3, the ACQ molecular weight dosage of the ACQ aqueous solution is 0.001% to 1% of the water weight dosage; The water in step S1, step S2 and step S3 is ultrapure water; the centrifugal speed is 3000 rpm to 6000 rpm, the centrifugal time is 5 min to 60 min, and the number of centrifugation is more than three times.

10. Use of the magnetic separation layer aggregation-induced luminescence coded microspheres according to any one of claims 1 to 6 in in vitro non-disease diagnosis and detection.

Citation Information

Patent Citations

  • Aggregation-induced emission magnetic fluorescent coding microsphere, preparation method and application thereof

    CN108587610A

  • Encoding microsphere and array, and preparation method

    CN112179885A